تقييم شبكات الصرف الصحي والمطري وفصل الشبكتين عن بعضهما في المنطقة الصناعية بمدينة طرطوس - وزان, أحمد (Latakia University Journal -Engineering Sciences Series, 2017)
نتيجة لتوسيع الشبكات الخاصة بالصرف الصحي و المطري لتخديم كافة المناطق في مدينة طرطوس وبالأخص المنطقة الصناعية التابعة لها لم يترافق بمعالجة سليمة لأعمال الصرف الصحي من فصل شبكة مياه صرف الأمطار عن شبكة الصرف الصحي وإنشاء محطات معالجة لمياه الصرف الصحي .ومع ازدياد عدد المصانع في المنطقة الصناعية , تزايد عدد السكان في مدينة طرطوس , الطلب على الحاجات الصناعية, الاستثمار السيئ للشبكات,انسداد الخطوط و التطاول عليها من خلال الخلط بين المعاشي و المطري و الصناعي,الهطولات الكبيرة لحوض مدينة طرطوس وصعوبة تصريف المياه المعاشية بالجريان الحر إلى محطة المعالجة, وعدم إمكانية تصريف مياه الأمطار ذات الغزارات الكبيرة .تم دراسة الوضع الراهن لخطوط الصرف المعاشي و الصرف المطري و الصناعي لوضع حلول لها.يوجد في المنطقة الصناعية شبكة صرف صحي ,تصب ضمن محطة معالجة خاصة بالمنطقة الصناعية وهي منفذة في المنطقة الواقعة جنوبي المنطقة الصناعية. وشبكة صرف مطري , تصب ضمن المسيل المائي الواقع جنوبي المنطقة الصناعية مع وجود شبكات موحدة و بعد دراسة وضعها الحالي . تم دراسة فصل الشبكات المطرية عن المعاشية في مناطق الشبكات الموحدة والصناعية لهذه المنطقة.As a result of the expansion of system of sewerage and rain water networks to serve all areas in Tartous city especially its industrial area, it was not associated with proper wastewater treatment including the separation of rainwater from sewage and building wastewater treatment plants. With the increased number of factories in the industrial area , the population growth in the city of Tartous, the demand for industrial needs, the poor investment for networks, the clogged lines and insulting them by mixing municipal, industrial and rainwater sewage and large precipitation for Tartous city Basin, and the difficulty of discharging wastewater according with gravity to the treatment plant And the lack of possibility to drain rain water with large flows, the study of the current situation of municipal, industrial and rainwater sewage to develop solutions for it. In the industrial area there is a sewage network which pours in the treatment plant in the industrial area and it is implemented in the southern region of the industrial area, and a rainwater network pours in the stream in the south of industrial area with a combined networks. After studying the current situation of these networks, we studied the separation of rainwater networks from the municipal networks in the combined and industrial networks areas.